A targeting algorithm for segregated heat integrated water allocation network. (September 2022) - Haider, Md Alquma; Chaturvedi, Nitin Dutt
Highlights: Presented methodology to target water and energy requirement in a segregated heat-integrated water allocation network. Developed algorithm is based on rigorously proven mathematical results. The proposed algorithm can handle zonal restrictions in allocation networks. The proposed algorithm is illustrated for single as well as multiple resources problems. Abstract: The exchange of resources is a critical step toward long-term viability and market economic strength. The use of Process Integration (PI) techniques has resulted in significant savings in resources. Industrial processes rely heavily on water and heat as input variables. Simultaneous conservation of heat and water is regarded as heat-integrated water allocation networks (HIWANs) in the PI. HIWAN problems may be identified for multiple zones. This leads to the specific problem known as segregated targeting problems (STPs), which are prevalent in various industries. Segregated targeting is characterised by the existence of multiple zones and a set of internal sources. The objective of this research is to address the HIWAN problem within the framework of STP to minimize heat and water consumption. The model's applicability is demonstrated by two illustrative examples, in which around a 20 to 65% reduction in resource requirements is reported when compared with the non-zonal integrated model.